Exploring Fire Safety Awareness Among The Malaysian Public - Sulaiman, Azim (2006)
Fire cases in Malaysia have been increasing rapidly over the years. Majority of the cases involved residential buildings which viciously had caused property losses, severe injuries to the victims and even caused death.